POLA PENGGUNAAN AIR UMBUL PANGLONG UNTUK KEHIDUPAN MASYARAKAT DI NAGORI PARIKSABUNGAN, KECAMATAN DOLOK PARDAMEAN, KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Yohanes Singal Lumban Gaol; Novdika Laurencia Pandiangan; Dani Raju Nasib Naibaho; Mardame Pangihutan Sinaga (Abdi Jurnal Publikasi, 2025)
This study examines the patterns of water usage from Umbul Panglong in Nagori Pariksabungan, Dolok Pardamean District, Simalungun Regency, North Sumatra Province. Data collection was conducted using a mixed-method approach, combining direct observation and interviews with several household heads representing diverse water users. The research findings classify water usage into three main categories: (1) Domestic needs, including drinking water consumption, cooking, bathing, and washing, which are the community’s top priorities; (2) Agricultural activities, particularly for irrigating rice fields and farms that support local food security; and (3) Productive economic activities such as fish farming, small-scale livestock raising, and home industries that require a clean water supply. Water usage patterns are influenced by factors such as water resource availability, seasonal variations, socioeconomic conditions, and local wisdom in natural resource management. The study reveals the existence of a traditional community-based water management system rooted in mutual cooperation (gotong royong), which has been practiced for generations. However, this system faces challenges due to changing weather patterns and increasing water demand. The existing water distribution system requires improvements to ensure more equitable and sustainable access.